Investigating professional identity construction of EFL teachers in informal language institutions through the lens of critical incidents - Rachelina Larasati; Concilianus Laos Mbato (Journal on English as a Foreign Language, 2025)
The professional identity of English as a foreign language (EFL) teachers in formal education has been widely studied, but research in informal education remains limited. This study explores the context of critical incidents (CIs) identified by informal language institutions (ILIs) EFL teachers and how EFL teachers in ILIs negotiate and construct their professional identities using the critical incident technique (CIT). Ten EFL teachers from an informal English course in Yogyakarta, Indonesia, participated through questionnaires and in-depth interviews. Data analysis identified key themes in CIs affecting teachers' professional identity. Results show that within informal language institution, CIs for teachers occurred in the context of the teacher's professional development, students, and direct work environment. The positive CIs, such as student progression and collaborative support, significantly boosted teachers' confidence and teaching effectiveness, whereas negative CIs, such as absenteeism and perceived inequities, posed challenges to their professional growth. Despite its limitations, including small sample size and reliance on self-reported data, the study provides valuable insights into the unique challenges and opportunities of teaching in informal educational settings, offering directions for future research and practical implications for teacher development programs.